Eco-Crimes and Ecocide at Sea: Toward a New Blue Criminology - García Ruiz, Ascensión (International journal of offender therapy and comparative criminology, 2022)
This essay adopts an interdisciplinary approach to consider the meaning of ?eco-crime? in the aquatic environment and draws on marine science, the study of criminal law and environmental law, and the criminology of environmental harms. It reviews examples of actions and behaviors of concern, such as offences committed by transnational organized crime and the legal and illegal over-exploitation of marine resources, and it discusses responses related to protection, prosecution and punishment, including proposals for an internationally accepted and enforced law of ecocide. One key element of the policy and practice of ending ecocide is the call to prioritize the adoption of technologies that are benign and renewable. Our essay concludes with a description of the ?Almadraba? method of fishing to illustrate that there are ways in which the principles of sustainability and restoration can be applied in an ethical and just way in the context of modern fisheries.